Determinants of the low use of Thailand’s Universal Coverage Scheme: a national cross-sectional study - Paek, Seung Chun; Zhang, Ning Jackie (Frontiers in Public Health, 2024)
IntroductionThailand’s Universal Coverage Scheme (UCS) has increased overall healthcare use by offering free healthcare for about 76% of the entire population since it was introduced in 2002. However, a considerable number of beneficiaries have continued to depend on private healthcare, and the low use of the UCS has been cited as a challenge to accomplishing the policy’s goal of universal access to healthcare. Thus, this study divided healthcare use into three patterns (self-medication, private providers, and UCS) and investigated the socio-demographic characteristics of non-users of the UCS and their reasons for non-use.MethodsA cross-sectional quantitative analysis was performed using data from the 2019 Health and Welfare Survey. UCS beneficiaries aged 15 years or older who had used healthcare during the past month were included in the sample. Descriptive analysis and multinomial logistic regression were performed to analyze associations between patterns of healthcare use and socio-demographic factors chosen based on Aday and Andersen’s access to medical care model.ResultsOf the study sample (n = 5,636), about 46.1% used healthcare services outside the UCS delivery system, of whom 33.8 and 12.3% used self-medication and private healthcare providers, respectively. Non-users generally had a higher socio-demographic status than UCS users. Specifically, they were young, had a high income, were employed, lived in urban areas, or did not have a chronic disease. The most common reason for non-use of the UCS was accessibility barriers (59.6%; e.g., long queues in public providers), followed by availability (25.4%; e.g., limited operating hours of public providers) and quality barriers (14%; e.g., unsureness of the quality of medicine offered by public providers). Moreover, self-medication users tended to be concerned about availability barriers, while private-provider users tended to be concerned about quality barriers for using the UCS.ConclusionUnder the UCS policy, there is a gap between the demands for healthcare and the resources assigned to increase the capability of public healthcare providers. That is, the UCS has increased financial accessibility for the use of the UCS (i.e., free healthcare from public providers). However, it probably has not yet increased healthcare resources and infrastructure facilitating the use of the UCS. This may have prevented the UCS from meeting the demands of its intended beneficiaries, especially those in high socio-economic groups, and ultimately forced them to use private healthcare.